Principles of public service in the decisions of the Constitutional Court of the Russian Federation - Софья Владимировна, Королева (NORTH CAUCASUS LEGAL VESTNIK, 2024)
Today, we can safely say that the state civil service is one of the most important institutions that ensures the implementation of public administration within the system of administrative and legal regulation. In modern realities, the requirements for the state civil service are constantly supplemented and improved. The essence of the state civil service is revealed through its principles. Despite the fact that a single approach to defining the principles of public service has not been adopted for the entire long history of the existence of the institution of public service, nevertheless, their key importance for the implementation of the institution of public service, as a rule, does not raise objections and even more so doubts. In this paper, we have considered several examples of scientific understanding of the principles of public service, and concluded that there is both scientific and normative content of the principles of public service. For many years, the entire system of public administration has been subject to reform. Despite the fact that the basic Federal Law "On the State Civil Service of the Russian Federation" has been in force for exactly 20 years, it is regularly amended. In recent years, a large number of by-laws have been adopted regulating the procedure for organizing and passing the state civil service. The state civil service primarily contributes to ensuring the foundations of the constitutional system and compliance with the Constitution of the Russian Federation, as well as the practical implementation of federal legislation and laws of the subjects of the Russian Federation. Constitutional and legal regulation determines the further development of legal regulation of all spheres of our life. It is the constitutional and legal foundations of the state service that allow us to understand the main directions of legal support for the state service. In this work, we came to the conclusion that we have been paying unreasonably little scientific attention to studying the implementation of the principles of state service in judicial practice. In this regard, it is important to analyze the legal positions of the Constitutional Court of the Russian Federation on issues of implementing the principles of state service.